Effect of the traditional parched rice husk incubation techniques on the hatchability of duck eggs - Khalequzzaman, M; Mahdi, Shah Hussain Ahmad; Rahman, M Mahbur (University Journal of Zoology, Rajshahi University, 2007)
The present study was carried out to know the seasonal effect on the hatchability of duck eggs in five private poultry farms at Gaibandha, Bangladesh. Eggs were set in artificial hatching bamboo made cylinders from different number of ducklings. Present observation revealed that the hatchability of duck eggs is highest in March (88.966 ± 2.11) and in June it is lowest (66.398 ± 0.63). In June the highest unfertilized eggs (25.532 ± 1.22) have been recorded followed by March (4.822 ± 0.68), January (10.164 ± 0.12), April (10.408 ± 0.31) and May (13.250 ± 1.37). The loss eggs were recorded highest in January (21.244 ± 1.36) and the lowest in March (4.874 ± 2.05). Least-square analysis of variance showed that individual months had significant effects on the hatchability of duck eggs. Key words: Duck egg, artificial incubation, hatching Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.37-40